Erodibility and erosion risk of black soils of central Mexico: study of a Phaeozem - Pérez-Salinas, Jesús Emmanuel; Rufino-Rodríguez, Fernando; Lopez-Santos, Armando; Torres-González, Jorge Alejandro; Meraz-Jiménez, Antonio de Jesús; Díaz-Romo, Abraham; Valdivia-Martínez, Oscar (REVISTA TERRA LATINOAMERICANA, 2019)
Erosion estimates for black soils in Mexico based on the Universal Soil Loss Equation (USLE) present discrepancies due to generalizations that lead to errors in permissible limits, with the erodibility factor or K factor (FK) being the most sensitive. The objective of the present investigation was to obtain a reasonable FK range for a Phaeozem (PH) from central Mexico by contrasting two equations based on the USLE. Samples were randomly obtained at three sites (P1, P2, P3) of a four-hectare area. The percentage of organic matter, textural class, soil structure, and profile permeability were determined. The results reveal differences between the estimated FK (FKe) and reference FK (FKr), whose values were +0.015, +0.028, and +0.029 for P1, P2, and P3, respectively. The differences represent underestimations that are up to 1.7 times greater in magnitude for FKr with respect to FKe. The statistical analysis rejects the null hypothesis (H0) that the means of each site evaluated are the same (P1 = P2 = P3). Although the variances between the factors of erodibility obtained using the equation specific to the Mollisols in Yunnan Province, China, and the reference nomography developed primarily in United States are significantly different (α ≥ 0.01), a combination of both could provide a range of maximums and minimums in the FK estimates and would yield better results than with the use of default values that tend to underestimate erosion rates.